2015
DOI: 10.1155/2015/362103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Iron Nitride Constructed by a Novel Template of Metal Organic Framework

Abstract: An iron nitride with high surface area was synthesized from an iron-based metal organic framework (Fe-MOF) in this work. During the synthesis process, the Fe-MOF of MIL-53 served as a hard template, a template to impart a certain degree of morphology for iron oxide products and to form porosities for iron nitride products. Moreover, it played the roles of iron sources for the synthesis of the final iron oxides and the iron nitrides. The physicochemical properties of the materials were characterized by a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 12 , 21 , 26 On the contrary, if sufficient solvent exchange occurs (exchange times >12 h), the MIL-53(Fe) can retain H 2 O molecules instead of DMF molecules (MIL-53(Fe)[H 2 O] form). 15 , 55 57 Based on the XRD results and the presence or absence of solvent exchange in the process, we can conclude that the MIL-53(Fe)_UTS retained DMF molecules (MIL-53(Fe)[DMF] form) and that the MIL-53(Fe)_UTS_H 2 O retained H 2 O molecules (MIL-53(Fe)[H 2 O] form) in their pore structures. Several studies have reported on the structure of the MIL-53(Fe)_solvo obtained via XRD analyses.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“… 12 , 21 , 26 On the contrary, if sufficient solvent exchange occurs (exchange times >12 h), the MIL-53(Fe) can retain H 2 O molecules instead of DMF molecules (MIL-53(Fe)[H 2 O] form). 15 , 55 57 Based on the XRD results and the presence or absence of solvent exchange in the process, we can conclude that the MIL-53(Fe)_UTS retained DMF molecules (MIL-53(Fe)[DMF] form) and that the MIL-53(Fe)_UTS_H 2 O retained H 2 O molecules (MIL-53(Fe)[H 2 O] form) in their pore structures. Several studies have reported on the structure of the MIL-53(Fe)_solvo obtained via XRD analyses.…”
Section: Resultsmentioning
confidence: 94%
“…In general, as the synthesis of the MIL-53­(Fe) proceeds in DMF, and the as-synthesized MIL-53­(Fe) retains DMF molecules in its pore structure (MIL-53­(Fe)­[DMF] form). If sufficient solvent removal or exchange of the as-synthesized MIL-53­(Fe) does not occur, the MIL-53­(Fe) still retains DMF molecules. ,, On the contrary, if sufficient solvent exchange occurs (exchange times >12 h), the MIL-53­(Fe) can retain H 2 O molecules instead of DMF molecules (MIL-53­(Fe)­[H 2 O] form). , Based on the XRD results and the presence or absence of solvent exchange in the process, we can conclude that the MIL-53­(Fe)_UTS retained DMF molecules (MIL-53­(Fe)­[DMF] form) and that the MIL-53­(Fe)_UTS_H 2 O retained H 2 O molecules (MIL-53­(Fe)­[H 2 O] form) in their pore structures. Several studies have reported on the structure of the MIL-53­(Fe)_solvo obtained via XRD analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [56] obtained Co@Co4N/MnO-NC by cracking the Mn-containing molecular sieve-imidazole framework. Liu et al [57] synthesized FeN using the iron foundation organic frameworks as the hard templates. However, as one of the most essential advantages of MOFs, high porosity can also bring a few disadvantages.…”
Section: Metal-organic Framework Methodsmentioning
confidence: 99%